Are we any closer to treating liver fibrosis (and if no, why not)? - Feng, Rilu; Yuan, Xiaodong; Weng, Honglei (Journal of digestive diseases, 2018)
This review provides a personal view on anti-fibrosis therapy in the liver. The worst clinical consequence of liver fibrosis is the development of liver cirrhosis and portal hypertension. Etiology is a decisive factor which determines patterns of fibrous septa and subsequent vascular remodeling, which is essential for the development of portal hypertension. Removing or controlling the disease-causing agent, i.e. anti-viral treatment for hepatitis, is the essential first step for treating chronic liver diseases and can reverse fibrosis in some settings. However, removing etiology is not always sufficient to prevent fibrosis from progressing towards cirrhosis and portal hypertension. In liver diseases such as severe alcoholic hepatitis and massive parenchymal loss, the formation of vascular anastomoses between portal to central veins based on bridging fibrosis results in cirrhosis and portal hypertension. For these patients, anti-fibrotic treatment is crucial and urgent. Unfortunately, a lack of understanding how fibrosis contributes to vascular remodeling caused by and combined with a lack of suitable experimental models that recapitulate human liver diseases, has hampered the development of successful anti-fibrotic drugs for clinical use to date.
Gesehen am 10.06.2020